KEUNGGULAN KOMPETITIF BISNIS KELUARGA DALAM BIDANG MANUFAKTUR PERIKANAN PADA MASA PANDEMI COVID-19: PT PLM [COMPETITIVE ADVANTAGE OF FAMILY BUSINESS IN FISHING INDUSTRY DURING COVID-19 PANDEMIC: PT PLM] - Felyana, Felyana; Tan, Jacob Donald (Milestone: Journal of Strategic Management, 2023)
PT PLM is a family company operating in the fisheries manufacturing industry which was able to survive and develop until it was able to win awards during the COVID-19 pandemic. The COVID-19 pandemic has had a significant impact on the manufacturing industry, one of which is a 30–40% decline in export demand in the production and distribution sector of fishery products. The research was conducted to find out the competitive advantages of PT PLM is still struggling to compete in the existing competition. This single case study research will be carried out qualitatively, where the data collection process will be carried out using interviews, observations, and field notes with informants, namely owners, employees, and customers from PT PLM hopes that their views can help and support in compiling the Mini-Model Theory in this research. It is hoped that the theory developed can help PT PLM in continuously improve its competitive advantage in the future and also provide insight into the world of academia in the fishing industry.Bahasa Indonesia Abstract: PT PLM merupakan perusahaan keluarga yang bergerak pada industri manufaktur perikanan yang mampu bertahan, berkembang hingga mampu meraih penghargaan selama pandemi COVID-19 terjadi. Padahal pandemi COVID-19 memberikan dampak yang signifikan terhadap industri manufaktur salah satunya seperti penurunan 30–40% permintaan ekspor pada sektor produksi dan distribusi produk perikanan. Penelitian dilakukan dengan tujuan untuk mengetahui keunggulan kompetitif yang dimiliki PT PLM yang hingga kini masih terus berjuang untuk berkompetisi di persaingan yang ada. Penelitian single study case ini akan dilakukan secara kualitatif, di mana proses pengumpulan data akan dilakukan menggunakan wawancara, observasi, serta catatan lapangan dengan informan yaitu pemilik, karyawan dan pelanggan yang berasal dari PT PLM yang diharapkan pandangan mereka dapat membantu dan mendukung dalam menyusun Mini-Model Theory di penelitian ini. Theory yang disusun diharapkan dapat membantu PT PLM dalam meningkatkan keunggulan kompetitifnya terus menerus di masa depan dan juga kasih wawasan untuk dunia akademia di industri perikanan tersebut.